Banglascapes in Southern Europe: Im-mobilities, emplacements, temporalities - Priori, Andrea; Mapril, Josè; Della Puppa, Francesco (Migration Letters, 2021)
This special issue stems from a panel we organised at the European Conference on South Asian Studies in 2018, under the title ‘Banglascapes in Southern Europe: comparative perspectives’. Not all the panel participants from that conference feature in this special issue, and not all the authors included here were present at the conference. Nevertheless, the panel represents a first important moment in which we began to collect case-studies and insights on a relatively new aspect of the so-called Bengali, or Bangladeshi, ‘diaspora’.